Letter from Hans Jolowicz to Max Bredig, October 13, 1945 - Jolowicz, Hans (1945)
Hans Jolowicz (1909-1987) writes to Max Bredig (1902-1977) regarding the tragic deaths of his brother-in-law and sister, Alfred Schnell (1900-1944) and Eva Schnell (1913-1944). Alfred Schnell was German chemist and formerly worked with Max Bredig in Berlin at the Bavarian Nitrogen Works. The Schnells, who were Jewish, were persecuted in Germany and sought refuge in the Netherlands during the Holocaust. They were eventually betrayed and killed by Dutch soldiers loyal to the Third Reich in 1944.
Keywords: Jolowicz, Hans, 1909-1987; Bredig, Max Albert, 1902-1977; Schnell, Alfred, 1900-1944; Schnell, Eva, 1913-1944; Jewish Holocaust (1939-1945)